Boron geochemistry of the geothermal waters from two typical hydrothermal systems in Southern Tibet (China): Daggyai and Quzhuomu. (November 2019) - Liu, Mingliang; Guo, Qinghai; Wu, Geng; Guo, Wei; She, Weiyu; Yan, Weide
Highlights: Remarkably high B concentrations were observed in some Tibetan geothermal waters. Magmatic fluids input and host rocks leaching contribute to the B in Daggyai waters. The source of B in Quzhuomu waters is dissolution of marine carbonates and granite. Multiple factors are responsible for the B enrichment in Tibetan geothermal waters. Abstract: The Tibetan plateau is characterized by a widely and intensively distributed geothermal activity and an extreme enrichment of boron in some geothermal waters. Twenty-five hot spring samples were collected from the Daggyai and Quzhuomu geothermal areas in Tibet to determine their boron concentrations and isotope composition. The boron concentrations and δ 11 B values for the neutral geothermal waters in Daggyai range from 72.5 to 106.9 mg/L and −16.4‰ to −12.3‰ while the Daggyai acid waters have much lower boron concentrations (1.1–1.2 mg/L) and slightly higher δ 11 B values (−12.9‰). The hot spring samples from the Quzhuomu geothermal area have boron concentrations varying from 21.9 to 44.6 mg/L and δ 11 B values from −11.3‰ to −7.1‰. The hydrochemical and B isotopic evidence imply that the boron in Daggyai geothermal waters is contributed by both magmatic fluid input and host rock leaching. In contrast, marine carbonates and granites, especially the former, are confirmed as the major boron sources for the Quzhuomu geothermal waters. In addition, there also exist some secondary processes affecting the boron isotope fractionation in geothermal waters, e.g. water-vapor separation and absorption or incorporation of B into hydrothermally altered minerals. Finally, based on the analysis of B geochemistry in these two typical geothermal areas in Southern Tibet with different heat sources and reservoir lithology, the mechanisms for the accumulation of boron in the Daggyai and Quzhuomu geothermal waters are suggested. This study is promising to provide insight into the sources of boron in the geothermal waters in other Tibetan geothermal areas.